Pengaruh Harga, Ketepatan Waktu Dan KualitasPelayanan Terhadap Kepuasan Pengguna Jasa Ekspedisi J&T Express Di Patokbeusi Subang - Lia Ardila; Bambang Irawan (JAMBIS : Jurnal Administrasi Bisnis, 2022)
The increasing use of e-commerce services during the pandemic influences the increasing need for expedition services, J&T Express. To survive in the intense competition, companies must maintain customer satisfaction. Based on a J&T Express customer complaints in Patokbeusi Subang survey, several customer dissatisfactions were obtained concerning the offered price, timely delivery, and the provided service quaility. This study aims to determine how much influence price, timeliness, and service quality have on user satisfaction at J&T Express expedition service in Patokbeusi Subang. The study uses the quantitative research method and questionnaires as the data collection technique, in which the calculation and data analysis is conducted using version 26 of the SPSS program. The results show that price has a positive and significant influence on user satisfaction by 14%, timeliness has a positive yet insignificant influence on user satisfaction by 1.2%, and service quality has a positive and significant influence on user satisfaction by 36.2%. Price, timeliness, and service quality altogether have a positive and significant influence on user satisfaction by 51.5.